Reactivation Viremia in Pediatric Sepsis*. Issue 4 (April 2020) - Han, Moonjoo; Roberts, Anna L.; Migliore, Brooke A.; Cárdenas, Ana María; Weiss, Scott L.
Abstract : Objectives: Reactivation viremia is associated with adverse clinical outcomes and immune dysfunction in adults with sepsis. We determined the incidence of viremia and its association with clinical outcomes and immune paralysis phenotype in children with severe sepsis. Design: Prospective cohort study. Setting: Single academic PICU from September 2016 to March 2018. Patients: Fifty-nine patients 2–17 years old treated for severe sepsis. Interventions: None. Measurements and Main Results: We performed real-time polymerase chain reaction assays on whole blood specimens to determine the incidence of cytomegalovirus. Cytomegalovirus was detected in three patients (5%). All patients with cytomegalovirus viremia were seropositive, with an incidence of 13% in this subset. We additionally performed Epstein-Barr virus and human herpesvirus-6 polymerase chain reaction assays on last available specimens and detected Epstein-Barr virus in 4% and human herpesvirus-6 in 30% of the study population. Overall, viremia was not associated with clinical outcomes or immune function in univariable analyses. However, viremia was associated with lower odds of complicated course (defined as death within 28 d or ≥ 2 organ dysfunctions at 7 d) after controlling for age, Pediatric Risk of Mortality III score, and blood transfusion (adjusted odds ratio, 0.08; 95% CI, 0.01–0.84; p = 0.04). Conclusions: Children with severe sepsis had low rates of detectable viremia, which limited analyses of its association with clinical outcomes or immune paralysis phenotype. Given the rare occurrence of cytomegalovirus viremia, in particular, our study does not support a role for viremia as a biomarker of illness severity or as a modifiable risk factor of clinical outcomes for most patients. Future studies on the role of viremia in pediatric sepsis will need to consider the challenges posed by low rates of viremia in this population. Abstract : Supplemental Digital Content is available in the text.